Hormone-Responsive BMP Signaling Expands Myoepithelial Cell Lineages and Prevents Alveolar Precocity in Mammary Gland - Shao, Chunlei; Lou, Pengbo; Liu, Ruiqi; Bi, Xueyun; Li, Guilin; Yang, Xu; Sheng, Xiaole; Xu, Jiuzhi; Lv, Cong; Yu, Zhengquan (Frontiers in Cell and Developmental Biology, 2021)
Myoepithelial and luminal cells synergistically expand in the mammary gland during pregnancy, and this process is precisely governed by hormone-related signaling pathways. The BMP signaling pathway is now known to play crucial roles in all organ systems. However, the functions of BMP signaling in the mammary gland remain unclear. Here, we found that Bmpr1a is upregulated by hormone-induced Sp1 at pregnancy. Using a doxycycline (Dox)-inducible Bmpr1a conditional knockout mouse model, we demonstrated that loss of Bmpr1a results in compromised myoepithelial integrity, reduced mammary stem cells and precocious alveolar differentiation during pregnancy. Mechanistically, Bmpr1a regulates the expression of p63 and Slug, two key regulators of myoepithelial maintenance, through pSmad1/5-Smad4 complexes, and consequently activate P-cadherin during pregnancy. Collectively, these findings identify a novel role of BMP signaling in maintaining the identity of myoepithelial cells and suppressing precocious alveolar formation.